COACHING CLINIC PENERAPAN MODEL PEMBELAJARAN KIDS ATLETIK DALAM PEMBELAJARAN PENDIDIKAN JASMANI DAN KESEHATAN DI KABUPATEN INDRAMAYU - Hidayat Humaid,; Tirto Apriyanto,; Agung Robianto,; Agus Salim, (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract The main target of the Faculty/Postgraduate Community Service (PPM-WBF) activities is physical education teachers in elementary schools in Indramayu Regency. Service activities are carried out by providing both theoretical and practical knowledge about PJOK teachers' knowledge about fostering athletic sports achievements for early childhood and increasing PJOK teachers' competencies about athletics. The participants of this activity were PJOK teachers as many as 33 participants. Community Service Activities in Faculty/Postgraduate Areas (PPM-WBF) have been carried out well. Community Service Activities in Faculty/Postgraduate Areas (PPM-WBF) Coaching Clinic The application of the Kids Athletic Learning Model in Physical Education and Health Learning in Indramayu Regency received an enthusiastic response from the participants of the activity. This is evident from the participation rate of activity participants of more than 100%. The level of satisfaction of PJOK teachers with this coaching clinic activity is very high, which is 89.24%. Keywords: Coaching Clinic, Kids Athletic, PJOK teacher Abstrak Sasaran utama kegiatan Pengabdian Kepada Masyarakat Wilayah Binaan Fakultas/Pascasarjana (PPM-WBF) adalah adalah guru-guru pendidikan jasmani di sekolah Dasar si Kabupaten Indramayu. Kegiatan pengabdian dilakukan dengan pemberian pengetahuan baik teori maupun praktek tentang pengetahuan guru PJOK tentang pembinaan prestasi olahraga atletik bagi anak usia dini serta peningkatan kompetensi guru PJOK tentang kids atletik. Peserta kegiatan ini adalah guru PJOK sebanyak 33 peserta. Kegiatan Pengabdian Kepada Masyarakat Wilayah Binaan Fakultas/Pascasarjana (PPM-WBF) telah terlaksana dengan baik. Kegiatan Pengabdian Kepada Masyarakat Wilayah Binaan Fakultas/Pascasarjana (PPM WBF) Coaching Clinic Penerapan Model Pembelajaran Kids atletik Dalam Pembelajaran Pendidikan Jasmani dan Kesehatan Di Kabupaten Indramayu mendapatkan respon yang antusias dari para peserta kegiatan. Hal ini terbukti dari tingkat partisipasi peserta kegiatan sebesar lebih dari 100%. Tingkat kepuasaan guru PJOK terhadap kegiatan coaching clinic ini sangat tinggi yaitu sebesar 89,24%. Kata kunci: Coaching Clinic, Kids Athletic, guru PJOK